A seventh child and the law - Yu, Patrick Shuk-siu (Hong Kong University Press, 1998)
This book talks about the description of the unique circumstances under which the author, as a matriculation student, was awarded a government scholarship to enter the University of Hong Kong in 1938, and consists of an accurate separate account of eight actual court cases handled by the author as Defence Counsel.